PEER TUTORING: A RESOURCE TO ENHANCE COLLABORATIVE LEARNING - Rodrigues, Lucas Andrey; Ribeiro, Jonatas Cavalcante; Oliveira, Thaize Soares (Seven Editora, 2025)
The present text describes a pedagogical experience of peer tutoring implemented in Middle School at SESI Dourados. It is a case study that demonstrates how interaction among classmates can enhance collaborative learning, student protagonism, and equity. The methodology consists of pairing students with greater mastery of the content with classmates facing difficulties, referred to respectively as “angels” and “mortals.” The experience revealed improvement in academic performance, especially in formative activities, and a reduction in status differences among students. The conclusions reinforce the importance of teacher mediation and the appreciation of multiple intelligences to promote more democratic and effective learning environments.DOI: https://doi.org/10.56238/sevened2025.038-035